(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم تحديد المكونات الكيميائية للزيت العطري لنبات الجعدة Teucrium polium var. mollissimum الذي ينمو في البيئة السورية بواسطة GC/MS. إذ تم الحصول على الزيت العطري بوساطة الجرف ببخار الماء، وتبين أنه يحتوي على 84 مكوناً مشكلة 93.06% من الزيت. وكانت المركبات الرئيسة هي: β-caryophyllene (12.33%), germacrene D (9.57%), 2-β-pinene (7.46%), trans-β-ocimene (6.99%), β-myrcene (5.21%), sabinene (5.11%), nerolidol (3.90%), bicyclogermacrene (3.41%), α-caryophyllene (2.64%), caryophyllene oxide (2.30%). Chemical components of the essential oil of the aerial parts of Teucrium polium var. mollissimum Hand-Mazz., grown in Syria has been determined by GC/MS. The oil obtained by hydrodistillation, is found to contain 84 components, accounting for 93.06 %. The major components determined were β-caryophyllene (12.33%), germacrene D (9.57%), 2-β-pinene (7.46%), and trans-β-ocimene (6.99%), β-myrcene (5.21%), sabinene (5.11%), nerolidol (3.90%), bicyclogermacrene (3.41%), α-caryophyllene (2.64%), and caryophyllene oxide (2.30%).